Factors associated with prelacteal feeding in North Eastern Ethiopia: A community based cross-sectional study. Issue 1 (December 2016) - Bililign, Nigus; Kumsa, Henok; Mulugeta, Mussie; Sisay, Yetnayet
Abstract Background In spite of the negative impact of prelacteal feeding on the growth and development of children, it is widely practiced in Ethiopia. This study aimed to assess prelacteal feeding practices and associated factors among mothers of children aged less than 24 months in the North Wello zone. Methods A quantitative community based cross-sectional study was employed during March 2015. Eight hundred and forty four (844) mother-child pairs were selected by multi-stage sampling technique. Data were collected by face-to-face interview. Descriptive statistics, binary and multiple logistic regression analyses were employed to identify factors associated with prelacteal feeding practice. Variables with ap -value <0.05 were identified as statistically significant factors. Results The prevalence of prelacteal feeding was 11.1 % (95 % confidence interval [CI]: 9.0, 13.0). Colostrum discarding (adjusted odds ratio [AOR]: 8.7; 95 % CI (3.8, 20.1)) and lack of counseling about breastfeeding (AOR: 2.6; 95 % CI 1.27, 5.4) were the factors associated with prelacteal feeding. The major reasons stated for providing prelacteal feeds were "culture" and "do not have enough milk". Conclusion Prelacteal feeds are offered to nearly one child in every ten in the North Wello zone. Colostrum removal and lack of counseling on breastfeeding at antenatal care visit are important positive predictors of prelacteal feeding practice. Awareness of the risks associated with prelacteal feeding, promotion of counseling on breastfeeding and the health benefit of colostrum during antenatal care visits are recommended interventions to reduce prelacteal feeding practices in the study areas.